Penerapan Pedoman Akuntansi Pesantren Menuju Good Islamic Boarding School Governance (Indonesian Journal of Dedication and Educations, 2023)
This community service aims to provide socialization and simulation related to Islamic boarding school accounting guidelines so that Islamic boarding schools can prepare and report their finances in accordance with applicable financial standards. Participants in this community service were administrators of Islamic boarding schools in Central Bangka Regency and South Bangka Regency, Bangka Belitung Islands Province. This community service method is socialization and material assistance as well as a simulation of the application of Islamic boarding school accounting guidelines. The speakers at this event were members of the IAI Bangka Belitung Islands Province and Lecturers at IAIN SAS Bangka Belitung. The result of holding this community service is that participants gain knowledge and knowledge about Islamic boarding schools accounting and participants can apply and stimulate Islamic boarding schools accounting and use student applications which can later be applied at their respective Islamic boarding schools.